2013
DOI: 10.1097/coh.0b013e32835fc68a
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming pharmacologic sanctuaries

Abstract: Purpose of review Current antiretroviral treatment regimens represent significant improvements in the management of HIV-1 infection; however, these regimens have not achieved a functional or sterilizing cure. One barrier to achieving a cure may be suboptimal antiretroviral concentrations in sanctuary sites throughout the body, including the central nervous system, gut-associated lymphoid tissue, lymph nodes, and tissue macrophages. This review will focus on the problems associated with achieving effective conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
104
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(107 citation statements)
references
References 58 publications
1
104
0
2
Order By: Relevance
“…Although several factors may contribute to the formation of the viral reservoir in the GALT, subtherapeutic concentrations of ARVs in the intestinal tissue and the potential for emergence of drug resistance may play a role in the observed local HIV replication. Indeed, previous studies have demonstrated that ARVs can have low and often subtherapeutic concentrations in lymphocytes isolated from the ileum and rectum-associated lymphoid tissue even in subjects receiving long-term ART who have undetectable plasma viral loads and that these low drug concentrations are associated with high viral counts detected in these tissues (10,11,43). Although tissue drug concentrations in the upper intestinal tract have not been investigated to date, formation of a viral reservoir is observed in GALT tissue isolated from the upper jejunum of HIV-infected subjects (6,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several factors may contribute to the formation of the viral reservoir in the GALT, subtherapeutic concentrations of ARVs in the intestinal tissue and the potential for emergence of drug resistance may play a role in the observed local HIV replication. Indeed, previous studies have demonstrated that ARVs can have low and often subtherapeutic concentrations in lymphocytes isolated from the ileum and rectum-associated lymphoid tissue even in subjects receiving long-term ART who have undetectable plasma viral loads and that these low drug concentrations are associated with high viral counts detected in these tissues (10,11,43). Although tissue drug concentrations in the upper intestinal tract have not been investigated to date, formation of a viral reservoir is observed in GALT tissue isolated from the upper jejunum of HIV-infected subjects (6,31).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies also suggest that poor drug penetration into these intestinal tissues may contribute to the lack of a local therapeutic response and the establishment of an HIV reservoir at this site (10,11). While drug transporters and metabolic enzymes are known to play a key role in drug disposition at the level of the intestinal epithelium and are suggested to contribute to the persistence of this viral reservoir, experimental evidence to support this rationale is currently lacking (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Il existe nĂ©anmoins une grande hĂ©tĂ©rogĂ©-nĂ©itĂ© entre ces molĂ©cules en ce qui concerne leur sĂ©questration par les protĂ©ines plasmatiques, leurs caractĂ©ristiques physico-chimiques et leur mĂ©tabolisation intracellulaire [14,35]. Le dĂ©veloppement de nouvelles molĂ©cules ayant de meilleures propriĂ©tĂ©s d'absorption intestinale, de distribution tissulaire et une demi-vie allongĂ©e comme le tĂ©nofovir alafenamide (TAF), commencent Ă  rĂ©pondre au problĂšme de sous-exposition du compartiment digestif au TARV [36]. Une autre option destinĂ©e Ă  juguler la rĂ©plication virale dans le GALT est l'intensification thĂ©rapeutique (Tableau I).…”
Section: Restaurer Le Taux De Lymphocytes T4unclassified
“…Apart from memory CD4 + T cells, HIV compartmentalization occurs both at the cellular level as well as different anatomical sites referred to as "viral sanctuaries" [60]. The CD4 + monocytemacrophage cell lineage including circulating monocytes, may contribute to the HIV reservoir.…”
Section: Challenges In Hiv Cure: the Hiv Latent Reservoirmentioning
confidence: 99%